FROM MINING REPUBLIC TO COLONIAL DISTRICT: THE POST COMPANY WAR TRANSFORMATION OF MONTERADO 1850-1879: Dari Republik Tambang Ke Distrik Kolonial: Transformasi Monterado Pasca-Perang Kongsi 1850-1879 - Andang Firmansyah; Mohammad Rikaz Prabowo; Hendar Prayoga (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the transformation of Monterado, Bengkayang Regency, from a gold mining center managed under the kongsi system to a Dutch colonial administrative region during the period 1850–1879. While previous research has touched on this aspect, there is a historiographical gap regarding an in-depth analysis of the drastic transition from a consensus-based governance system to a hierarchical colonial bureaucracy, and the impact of this transformation until the late 1870s. Using historiographical methods through economic, political, and sociological approaches, this study analyzes the dynamics of the collapse of the gold kongsi and its impact on the socio-economic structure of the community. The findings indicate that internal conflicts between kongsi due to the depletion of gold reserves, Dutch military intervention through the Kongsi War (1850–1854), and the formal dissolution policy in 1854 were the main factors behind the collapse of the kongsi system. The dissolution triggered a mass migration of approximately 4,000 refugees to Sarawak and thousands more to coastal areas of West Kalimantan. This transformation ended the democratic kongsi government that had existed since 1776 and replaced it with a hierarchical colonial bureaucracy, placing the assistant resident as the highest authority. The main contribution of this research is to fill the narrative gap regarding the process of social disintegration and demographic reorganization, and to explain the roots of the formation of a hybrid Chinese-Malay identity in the coastal region by tracing three waves of post-war migration. These fundamental changes not only reshaped the political landscape but also created economic decline and structural dependence on the colonial government with long-term consequences.